A New Quantity to Characterize Stochastic Resonance *Supported by the National Basic Research Program of China under Grant Nos 2011CB922104 and 2011CBA00202, the National Natural Science Foundation of China under Grant No 11474154, the Natural Science Foundation of Jiangsu Province under Grant No BK2012013, the Specialized Research Fund for the Doctoral Program of Higher Education of China under Grant No 20120091110030, the Dengfeng Project B of Nanjing University and Jiangsu Key Laboratory of Advanced Manipulating Techniques of Electromagnetic Waves, and the Priority Academic Program Development of Jiangsu Higher Education Institutions. (September 2015) - Wang, Yu-Xin; Zhai, Ji-Quan; Xu, Wei-Wei; Sun, Guo-Zhu; Wu, Pei-Heng
<x content-type="archive" xml:space="preserve">Abstract</x> In a double-well system, we investigate theoretically the population distribution of a particle perturbed by a weak sinusoidal signal with a Gaussian white noise accompanied. Our numerical simulation shows that the probability of the particle staying in the right potential well, PR, exhibits an extreme value at specific noise intensity D depending on the frequency of the sinusoidal signal, which is a key feature of stochastic resonance. This is confirmed by calculating the power spectrum of the output signal, in which the extreme value of the amplitude locates at the same noise intensity. These results provide us with a new way to quantify the stochastic resonance by measuring the population distribution of the particle.